Registered Dietitian Nutritionists Are Associated with Improved Long-Term Clinical Outcomes in High-Risk Patients. (29th May 2020) - Cavanaugh, Erika; Zeman, Heather; Metallinos-Katsaras, Elizabeth; Strowman, Shelley; Ireland, Kathy; Pojednic, Rachele
Abstract: Objectives: Treatment from registered dietitian nutritionists (RDNs) has been shown to improve weight and hemoglobin A1c in high-risk patients, yet little is known about these outcomes long term. The current study investigated the association between RDN care and changes in weight and HbA1c compared to primary care in high-risk patients (BMI ≥35 kg/m 2 or HbA1c ≥7%) long term up to 24 months. Methods: This was a retrospective cohort study of high-risk adults. Electronic medical records were reviewed for participants who were 18 years or older with BMI ≥35 kg/m 2 or HbA1c ≥7.0% at first visit to a patient centered medical home in Boston, MA. Mean change in weight (kg) and HbA1c (%) at six, 12, and 24 months were compared between patients who saw an RDN and patients who received primary care only. Paired sample t-tests and repeated measures ANOVA adjusting for age, sex, gender, days from baseline at follow-up visit, and number of clinic visits at follow-up were used to analyze outcomes. Results: 1902 patients with BMI >35 and 1240 patients with a HbA1c >7.0% were included. There was no significant difference in 24-month weight loss between RDN care and standard primary care. HbA1c decreased significantly with RDN care at all time points ( P  < 0.001). Patients with at least one RDN visit had a significantly greater mean change in HbA1c of −0.8 ± 0.2 (95% CI −1.0 to −0.5) and −0.6 ± 0.1 (95% CI −0.8 to −0.3) after 12 and 24 months from baseline, respectively ( P  < 0.001). Conclusions: RDN care resulted in statistically and clinically significant improvements in HbA1c at 12 and 24 months compared to standard primary care alone. Funding Sources: The authors received no specific funding for this work.